FMCE-PHQ-9 Assessment with Rasch Model in Detecting Concept Understanding, Cheating, and Depression amid the Covid-19 Pandemic - Sulman, Fauzan; Sutopo, Sutopo; Kusairi, Sentot (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This research aims to see the ability of the FMCE-PHQ-9 test instrument amid the Covid-19 pandemic to measure conceptual understanding, cheating, and depression in students. The research was conducted on 64 physics education students at Sulthan Thaha Saifuddin State Islamic University Jambi. The instrument consists of 47 force and motion material items to fit the Winsteps 3.65.0 program. The analysis results using the Rasch Model showed that the MNSQ Outfit was 1.00 in the person column and 0.1 in the item column. Judging from the ZSTD value of 0.57 for the person and 0.1 for the item, the Points Measure value correlated with 0.4 to 0.85 while the item reliability value was 0.73 and the Cronbach's Alpha value was 0.56. therefore, the test instrument using the Rasch proclamation model found 31 fit items. The analysis results show that the concept ability was poor since, on average, the students could only answer questions with a low index of difficulty category. The research results on the level of cheating obtained data that 100 percent of students were not indicated to have the same pattern. Lastly, for the level of depression, only 16 percent of students did not experience depression, while 84 percent of students experienced it.